THE IMPACT OF FINANCIAL AND NON-FINANCIAL COMPENSATION ON THE JOB SATISFACTION OF PT. DEMPO ANDALAS SAMUDERA PADANG EMPLOYEES - Alparedi, Topan; Febi, Zebna; Mursal, Mursal; Bustomi, Ahmad (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: This research aims to obtain real evidence of the influence of financial and non-financial compensation on job satisfaction PT. Dempo Andalas Samudera Padang employees. Desain/Methodology/Approach: A sample of 67 employees who received financial and non-financial compensation was used for the test. Sample selection was carried out using the survey method. Hypothesis testing uses inferential analysis through multiple linear regression models and t-statistical tests. Findings: The test results showed that the first hypothesis was accepted, namely that financial compensation had a significant effect on job satisfaction, and the second hypothesis was also accepted, namely that non-financial compensation had a significant effect on job satisfaction. Research Implications: This research proves that good compensation can increase employee satisfaction. Therefore, companies need to formulate financial and non-financial compensation for their employees.